1999
DOI: 10.1111/j.1532-5415.1999.tb01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Levels of Dehydroepiandrosterone Sulfate, but Not Other Sex Hormones, Are Associated with Depressed Mood in Older Women: The Rancho Bernardo Study

Abstract: These results add to the evidence that DHEA/S is a neuroactive steroid and point to the need for careful long-term clinical trials of DHEA therapy in older women with depressed mood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
142
6
4

Year Published

2001
2001
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 211 publications
(160 citation statements)
references
References 78 publications
8
142
6
4
Order By: Relevance
“…There is a positive correlation between reduced serum DHEAS levels and lower bone mineral density in the spine, hip and radius in women aged 45±69 years (11), but no such effect is noted in men (12). In the central nervous system, lower DHEAS levels are associated with depressed mood in older women but not men (13), and a higher cortisol/ DHEA ratio correlates with cognitive decline in both sexes (14). There are con¯icting reports of lower DHEAS levels in Alzheimer's disease (15,16).…”
Section: Dhea Replacement In Ageingmentioning
confidence: 83%
“…There is a positive correlation between reduced serum DHEAS levels and lower bone mineral density in the spine, hip and radius in women aged 45±69 years (11), but no such effect is noted in men (12). In the central nervous system, lower DHEAS levels are associated with depressed mood in older women but not men (13), and a higher cortisol/ DHEA ratio correlates with cognitive decline in both sexes (14). There are con¯icting reports of lower DHEAS levels in Alzheimer's disease (15,16).…”
Section: Dhea Replacement In Ageingmentioning
confidence: 83%
“…Depressed patients have lower levels of plasma DHEA sulfate (DHEAS) (Barrett-Connor et al, 1999;Goodyer et al, 1998) and of saliva DHEA (Fabian et al, 2001;Takebayashi et al, 1998) than controls. Moreover, lower saliva DHEA levels in the morning correlate negatively with the severity of depression (Michael et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these associations are somewhat modified by ethnicity (Santoro & Crawford, personal communication, March 2006) and deserve closer scrutiny. Barrett-Conner et al reported that serum DHEAS level but not that of any other sex steroid was associated with depressed mood in older women [5].…”
Section: Introductionmentioning
confidence: 99%